Retrospective 3-dimensional evaluation of skeletal and dental structures following treatment with hybrid hyrax-mentonplate with class III elastics in class III patients with vertical Growth Pattern: A pilot study - YILDIRIM, GAMZE; ÖNEM ÖZBİLEN, ELVAN (My University, 2023)
Objective: The aim of the present study is to evaluate the skeletal and dental changes three-dimensionally in patients with skeletal Class III malocclusion and vertical growth pattern treated with hybrid hyrax-mentoplate and Class III elastic combination. Materials and Methods: In this retrospective study, conebeam computed tomography images of 6 patients (5 females and 1 male; Mean age: 11.9±0.9 years) who had undergone an orthopedic treatment with hybrid hyrax-mentoplate and Class III elastic combination were retrieved from the archive of Marmara University, Department of Orthodontics. Initial and post-protraction skeletal and dental parameters were investigated by using 3D SLICER version 5.0.2 software (www.slicer.org). Statistical significance was set at p<0.05. Results: Sagittal skeletal evaluation showed statistically significant increases of 2.31° in SNA, and 2.8° in ANB (p<0.05), with no significant change in SNB (p>0.05). There were no significant changes in vertical skeletal parameters except significant decreases in FH-OP and SN-OP angles of 5.28° and 5.18°, respectively. In terms of dental changes, while a significant decrease was found in LI-OP angle (8.82°), significant increases in LI-MP angle and in overjet change were found (5.27°, 3.75 mm, respectively) (p<0.05). There were no significant changes in upper incisor parameters, UI-LI angle, and overbite (p>0.05). A significant increase was found in both SN-16M and SN-26M (5.79 mm, 4.10 mm, respectively) (p<0.05), while a significant decrease was observed in MP-36M and MP-46M measurements (1.62 mm, 2.29 mm, respectively) (p<0.05). Conclusion: With the use of hybrid hyrax-mentoplate and Class III elastic combination, orthopedic sagittal correction can be achieved in patients presenting high angle skeletal Class III without causing any changes in facial height, and the slope of mandibular and palatal planes

Amaç: Bu çalışmanın amacı, hibrit hyrax-mentonplak ve Sınıf III elastik kombinasyonu ile tedavi edilen iskeletsel Sınıf III maloklüzyonlu ve vertikal yönde artmış büyüme paterni olan hastalarda meydana gelen iskeletsel ve dental değişiklikleri üç boyutlu olarak değerlendirmektir. Gereç ve Yöntemler: Bu retrospektif çalışmada hibrit hyraxmentonplak ve Sınıf III elastik kombinasyonu ile ortopedik tedavi görmüş 6 hastanın (5 kadın ve 1 erkek, Ortalama yaş: 11,9±0,9 yıl) Konik Işınlı Bilgisayarlı Tomografi görüntüleri, Marmara Üniversitesi Ortodonti Anabilim Dalı arşivinden alınmıştır. Başlangıç ve protraksiyon sonrası iskeletsel ve dental parametreler 3D SLICER versiyon 5.0.2 yazılımı (www.slicer.org) kullanılarak incelenmiştir. İstatistiksel anlamlılık p<0,05 olarak belirlenmiştir. Bulgular: Sagital iskeletsel değerlendirmede SNA açısında 2,31° ve ANB açısında 2,8° istatistiksel olarak anlamlı artış bulunurken (p<0,05), SNB açısında anlamlı değişiklik bulunamamıştır (p>0,05). Vertikal iskeletsel değerlendirmede FH-OP ve SN-OP açılarında sırasıyla 5,28° ve 5,18° anlamlı azalma gözlenirken (p<0,05), diğer vertikal iskeletsel ölçümlerde anlamlı bir değişiklik bulunmamıştır (p>0,05). Dental değerlendirme parametrelerinden, LI-OP açısında 8,82° anlamlı azalma, LI-MP açısında 5,27° artış ve overjet değişiminde 3,75 mm anlamlı artış gözlenmiştir (p<0,05). Üst keser açıları, UI-LI açısı ve overbite ölçümlerinde anlamlı bir değişiklik bulunamamıştır (p>0,05). Hem SN-16M hem de SN-26M’de (sırasıyla 5,79 mm ve 4,10 mm) (p<0,05) anlamlı artış bulunurken, MP-36M ve MP-46M ölçümlerinde (sırasıyla 1,62 mm ve 2,29 mm) (p<0,05) anlamlı azalma gözlenmiştir. Sonuç: Hibrit hyrax-mentonplak ve Sınıf III elastik kombinasyonu uygulaması ile iskeletsel Sınıf III maloklüzyonlu ve artmış vertikal büyüme paternli hastalarda, yüz yüksekliğinde değişiklik olmaksızın ve mandibular ve palatal düzlemde rotasyon gözlenmeksizin sagittal yönde ortopedik düzeltme sağlanabilmektedir.
Dikey büyüme paterni olan sınıf III hastalarda sınıf III elastiklerle hibrit hyrax-mentonplak tedavisi sonrası iskeletsel ve dental yapıların retrospektif olarak 3 boyutlu değerlendirilmesi: Bir pilot çalışma
Keywords: Diş Hekimliği; Klinik Bilimler; Ortodonti; Sağlık Bilimleri; Dentistry; Clinical Sciences; Orthodontics; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Ortodontik Tespit İşlemleri; OrtodontiDüzeltici; Ortodontik Alet Dizaynı; Orthodontic Anchorage Procedures; OrthodonticsCorrective; Orthodontic Appliance Design